1970
DOI: 10.2134/agronj1970.00021962006200040039x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of 2‐Chloro‐6‐(Trichloromethyl) Pyridine in Soybean (Glycine Max L. Merr.) Seedlings1

Abstract: Soybeans were grown for 18 days in a silt loam soil containing 0 to 20 ppm 2‐chloro‐6‐(trichloromethyl) pyridine (N‐Serve). Yield of shoots was reduced by concentrations of 8 and 20 ppm and their morphology was altered with concentrations as low as 1 ppm. Yield of roots was not greatly affected by up to 20 ppm, but their morphology was drastically altered with 8 and 20 ppm. Production of NO3 in the soil was reduced 90% by 8 and 20 ppm, 60% by 3 ppm and only slightly by 1 and 0.5 ppm of 2‐chloro‐6‐(trichloromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1973
1973
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Significantly lower yields were recorded with AS 2 +N-Serve compared with AS 2 under low irrigation conditions in both soil types, while in Piarco soil AS 1 +N-Serve gave significantly lower yield than AS 1 • It appears that N-Serve at high rate and/or under dry conditions can be toxic to cane, especially in the sandy soil. Toxic effects of N-Serve on other plants have been reported by other workers (5,10,11 ). No consistent effect of N-Serve on tillering was evident ( Table 2).…”
Section: Drum Experimentssupporting
confidence: 49%
“…Significantly lower yields were recorded with AS 2 +N-Serve compared with AS 2 under low irrigation conditions in both soil types, while in Piarco soil AS 1 +N-Serve gave significantly lower yield than AS 1 • It appears that N-Serve at high rate and/or under dry conditions can be toxic to cane, especially in the sandy soil. Toxic effects of N-Serve on other plants have been reported by other workers (5,10,11 ). No consistent effect of N-Serve on tillering was evident ( Table 2).…”
Section: Drum Experimentssupporting
confidence: 49%
“…Because 6chloropicolinic acid is the initial and principal metabolite present after the application of nitrapyrin, some of the phytotoxicity observed in studies conducted with nitrapyrin is probably due to 6-chloropicolinic acid. This would seem to be the case in instances where auxin-type symptoms have been observed with leguminous plants (6,7,12,13).…”
mentioning
confidence: 93%
“…Results obtained in several laboratory studies, however, have shown that nitrapyrin applied to soil can produce phytotoxicity, and that the nature and sev-erity of the phytotoxicity depends to a large extent upon the concentration of nitrapyrin as well as the plant species and soil in question (6,7,9,12,13). Legumes such as alfalfa (Medicago sativa L.) (7), black locust (Robinia pseudoacacia L.) (6,12), and soybean [Glycine max (L.) Merr.]…”
mentioning
confidence: 99%
“…A decrease in main root elongation and lateral root formation due to nitrapyrin has been reported by Lynd et al (1967). Riley and Barber (1970) found that 8 and 20 ppm nitrapyrin caused soybean roots to be stubby and form club-like swelling, particularly just behind the root tips.…”
Section: Resultsmentioning
confidence: 69%
“…was 10 ppmw, which is well above the concentration resulting from application of highest recommended rate. Riley and Barber (1970) reported that yield of soybean shoot was reduced with nitrapyrin concentrations of 8 and 20 ppm and its morphology was changed with concentration as low as 1 ppm. The nature and severity of nitrapyrin toxicity varies with concentration (Gerónimo et al, 1973;Mills et al, 1973), plant species (Gerónimo et al, 1973; Osborne, 1977; Sander and Barker, 1978), and soil properties (Gerónimo et al, 1973).…”
mentioning
confidence: 99%